Accuracy of mandibular vertical linear measurement in panoramic and tomography images - Ehsan Moudi; Sina Haghanifar; Hoora Hadian; Ali Bijani; Mirmahmood Safinia; Nika Bahemmat (Babol University of Medical Sciences, 2013)
Introduction: The measurement precision of jaw is important for surgery or installing implants. Preimplant radiographs are important part of clinical evaluations before implant surgery. For choosing location, we should consider the important anatomical structures like mental foramen, inferior alveolar canal, nasal cavity and maxillary sinus.It is important to know the measurement accuracy of radiographic techniques. The purpose of this study was to compare mandibular vertical linear measurement in panoramic and tomography images. Methods: Three forms of mandible from dry adult human skulls were used in this study (triangle, square and ellipse). For each mandible, surgical stent was made using transparent with gold standard.acryl. A thin tube was placed in the stents in three regions (incisors, premolars and molars) to set gutta-percha. Then, the panoramic view and conventional tomography were obtained. Four oral and maxillofacial radiologists measured the vertical dimension in panoramic and conventional tomography. Finally, each mandible was sectioned in the marked sections and was measured by a digital caliper (gold standard) and compared with conventional tomography and panoramic view .The obtained data was analyzed using SPSS18 software and student t-test, Pearson correlation coefficient and non parametric Mann-Whitney Test. Results: The mean difference between the panoramic and gold standard linear vertical dimension values in premolar and molar regions was above 1mm and above 2mm in incisor region. The mean difference between conventional tomography and gold standard measurements in all three regions was 1mm. Conclusions: The linear measurement of vertical dimension in conventional tomography was more precise than panoramic. The use of a 2.0 mm safety margin in the evaluation of implant sites was recommended.In incisor area, the other radiography methods like CBCT was suggested.